(untitled) (Indian Journal of Animal Production and Management, 2024)
Rumination is the process of regurgitation, re-mastication, salivation and swallowing of ingesta. Cows ruminate for approximately 504±93 min/day and a decrease in rumination time is typically important sign that something is affecting ruminal function and cow well-being. Rumination activity mainly occurs at night and during resting periods in the afternoon. Rumination can be detected by the several methods viz. visual observation, video recording, nose band pressure signal, accelerometer ear-tags and neck collar. The time that an animal spends ruminating is influenced by species, breed, physical & chemical characteristics of the diet, health condition, feed intake and production level. More roughage diet with long fibre increases the rumination time. Diets containing higher neutral detergent fibre (%) resulted in increase in rumination time per kilogram of roughage ingested. Rumination time decrease with increasing temperature humidity index. Rumination time significantly influence the milk yield and milk composition and reproduction performance. Rumination time could be used to monitor dairy cattle during calving, oestrous, and heat stress, as well as to detect diseases, heat stress, transition cow disorders and subclinical ketosis in dairy cows.